A Crowdfunding sebagai Instrumen Investasi Baru: Analisis Yuridis terhadap Perlindungan Investor di Indonesia - Romeo Andrano Andrano; Ikarini Dani Widiyanti; Pratiwi Pusphito Andini (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
This study aims to analyze the legal protection of investors in crowdfunding as a new investment instrument in Indonesia. The rapid growth of financial technology has introduced crowdfunding platforms as alternative financing and investment schemes beyond conventional capital markets. However, this development raises legal risks for investors, including information asymmetry, potential fraud, and default by issuers. This research uses a normative juridical method with statutory and conceptual approaches, supported by comparative studies with international practices. The results indicate that the Indonesian regulatory framework, mainly the Financial Services Authority Regulation (POJK) No. 57/POJK.04/2020, has provided preventive protection through licensing requirements, disclosure obligations, and monitoring mechanisms. Nonetheless, repressive protection mechanisms remain limited, particularly regarding dispute resolution and liability of platform providers. This study concludes that while crowdfunding is a promising instrument for democratizing investment, legal certainty and investor protection need to be strengthened by expanding OJK’s supervisory role and harmonizing crowdfunding regulations with capital market and company law.